Whose House?: Revisiting the Referent of autu͂ in Mark 2.15 - Ålöw, Tobias (Journal for the study of the New Testament, 2026)
The referent of αὐτοῦ in Mk 2.15 is grammatically ambiguous and remains a point of scholarly debate. Does Mark say that Jesus attended a banquet in Levi's house, or that Jesus hosted one in his own home, with Levi and others as his guests? The current status quaestionis is basically undecided and timeworn arguments keep being rehearsed. Accordingly, this article attempts to move the conversation forward by revisiting some previously touched-upon yet underexplored notions of Mark?s presentation. After reviewing prior arguments, it first adopts a social-scientific lens to show that Jesus is portrayed as host - a role that, in context, implies ownership of the house. Thereafter, adopting a narratological approach, the study analyzes Mark's use of "house" demonstrating that the idea of Jesus having a house aligns with Mark's broader characterization of Jesus, is supported by several other references to a Capernaum residence, and reflects a pattern according to which house owners are typically named - except in 2.15 - thus, implying the house is Jesus's. Taken together, these observations support the conclusion that according to Mk 2.15 the house was Jesus's.